Evaluation of Diagnostic Delay in Emergency Urological Cases at a General Hospital Emergency Department - Khaeriah B; Andi Dedi Pradana Putra (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
This study aims to evaluate the diagnostic delays in emergency urological cases at a general hospital emergency department (ED). Using a qualitative research approach and a literature review methodology, the study analyzes existing research articles, medical journals, and case studies focusing on diagnostic delays in urological emergencies. The findings indicate that diagnostic delays are prevalent in EDs, primarily due to factors such as insufficient specialized knowledge among emergency physicians, communication breakdowns, overcrowding, and limited access to diagnostic tools. These delays have serious consequences, including worsened patient outcomes such as kidney damage, testicular loss, and increased risk of sepsis. The study also identifies several strategies to reduce diagnostic delays, including improving training for emergency department staff, enhancing communication between medical teams, and integrating technology, such as telemedicine and AI-assisted diagnostic tools. The review highlights that addressing these factors through targeted interventions could significantly improve diagnostic accuracy and reduce delays, ultimately leading to better patient outcomes. Moreover, the research provides insights into the systemic challenges within EDs that contribute to delays, including overcrowding and inadequate staffing. The study’s findings emphasize the need for hospitals to adopt evidence-based practices to optimize diagnostic procedures and improve the efficiency of emergency care. This study contributes to the ongoing efforts to improve the quality of care in urological emergencies and underscores the importance of timely diagnosis in preventing severe complications.